Bullying Prevalence among Secondary School Children in Khamis Mushait City, Southwestern Saudi Arabia - Mohammed Abadi Alsaleem; Huda Aied Alhashem; Safar Abadi Alsaleem; Ahmed A. Mahfouz (Behavioral Sciences, 2021)
Bullying is a type of behavior that involves frequent, hostile activities expected to harm another person physically, mentally, or emotionally. Bullying behavior uses force, pressure, or threats to maltreat, forcefully dominate, or terrify another individual. The aim of this study was to assess the bullying prevalence and related features among secondary school pupils in Khamis Mushait city, southwestern Saudi Arabia. A cross-sectional investigation was performed among governmental and private secondary schools in Khamis Mushait city. Data were gathered from the study pupils using a pre-structured questionnaire. Bullying was assessed using the school climate bullying survey. The study included 300 secondary school students (163 females and 137 males). The overall rate of bullying was 64.7% (95% CI 59.1–69.9). The most prevalent type of bullying was verbal (41.7%, 95% CI 36.0–47.5) followed by physical (17.0%, 95% CI 12.9–21.7), and social (6.0%, 95% CI 3.6–9.3). Males had more than two times greater probability of having been bullied than females (aOR = 2.522, 95% CI 1.408–4.518). Similarly, students in first-level grade classes had more than three times greater probability of being bullied victims than those in the higher classes, i.e., second- and third-level grade classes (aOR = 3.417, 95% CI 1.159–10.07). More than half of the students tell teachers when other students are being bullied (53.7%) and tell a teacher or staff member at the school if they are being harassed (53.6%); teachers are doing anything they can to help if they are told that a student is being bothered (58.7%), and teachers are making clear to students that bullying is not tolerated (52.3%). In conclusion, in the present study, we reported a high prevalence rate of bullying among secondary school pupils in Khamis Mushait city, southwestern Saudi Arabia. Concerted efforts among teachers and health care providers in the region should be mandatory to deal with the problem.